Adherence to thrombophilia testing guidelines and its influence on anticoagulation therapy: A single-center cross-sectional study. Issue 223 (March 2023) - Vrotniakaite-Bajerciene, Kristina; Tritschler, Tobias; Jalowiec, Katarzyna Aleksandra; Broughton, Helen; Schmidli, Fabienne; Schneider, Jenny Sarah; Haynes, Alan; Rovo, Alicia; Hovinga, Johanna Anna Kremer; Aujesky, Drahomir; Angelillo-Scherrer, Anne
Abstract: Introduction: The collected evidence on thrombophilia guidelines is scarce and data about their impact on clinical decisions are unknown. We aimed to investigate the adherence to thrombophilia testing guidelines, its therapeutic impact in patients with guideline-adherent and non-adherent testing and identify the patients' clinical characteristics mostly associated with treatment decisions. Materials and methods: We conducted a single-center cross-sectional study of patients referred for thrombophilia testing at the outpatient clinic of a tertiary hospital between 01/2010–10/2020. We systematically evaluated the adherence of thrombophilia testing to internal guidelines and the influence of test results on anticoagulation therapy. Using multivariable logistic regression, we evaluated the association between clinical characteristics and influence of thrombophilia tests on anticoagulation therapy in the entire cohort and by indication for referral. Results: Of 3686 included patients, mostly referred for venous thromboembolism (2407, 65 %) or arterial thrombosis (591, 16 %), 3550 patients (96 %) underwent thrombophilia testing. Indication for testing was according to guidelines in 1208 patients (33 %). Test results influenced treatment decisions in 56 of 1102 work-ups (5.1 %) that were adherent to guidelines, and in 237 of 2448 (9.7 %) non-adherent work-ups (absolute difference, 4.3 %; 95 % confidence interval, 2.9–6.3 %). Age < 50 years, female sex, absence of risk factors and co-morbidities, weakly provoked venous thromboembolism and referral indication other than venous thromboembolism were associated with influence on anticoagulation therapy. Conclusions: Adherence to guidelines for thrombophilia testing was poor and did not have an impact on treatment decisions. Refinement of selection criteria is needed to increase the therapeutic impact of thrombophilia testing. Highlights: The therapeutic impact of recommended thrombophilia testing strategies is uncertain. We conducted a cross-sectional study of 3686 patients during a 10-year period. Thrombophilia work-up was adherent to guidelines only in 33 % tested patients. Adherence was not associated with influence on anticoagulation treatment. Testing in weakly provoked VTE was associated with prolonged anticoagulation.